(3bhGWY GdCOdI aj GdQO Ydi GdhLhOjIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdedJLC Edi MQe QHg GdHGQF Ydi Hf SdWGf eMeO GdbGQi Gfg hQO SDGd ef UGMH MGd eVehfg Gfg bGd HYV Lgdg GdeJUhaI s
(3BNQgG (B:s
(3bHd GdcTa ef GdCJHGY hGdEbJOGA hjCeQhf CUMGHge HEdJRGegG hgcPG jfHZi Cf jchf MGd GdeQjO CYde HMbjbI GdMGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI O(B/ (3eMeO UOjb GdLdjdi (B_ (3GdehUd s
Keywords: (3GdJhMjO hGdedd hGdfMds